LOCATION MODEL OF COAL BLENDING FACILITIES TO ENSURE COAL SUPPLY FOR COAL FIRED POWER PLANTS IN JAVA ISLAND - Ikhsan Pratama, Hanif
In the RUPTL 2015-2024 document (2015-2024 Indonesia’s Electricity Supply Business Plan) of PT. PLN (Persero), there is a plan for fulfillment of the national electricity needs of medium-term (2015-2019), known by the name of 35.000 MWs Power Plant Project. The majority of plant type from the project that as many as 19.940 MWs is a Coal Fired Steam Power Plant. In operating a Power Plant, the continuity of fuel supply is an important factor. The mechanism of coal supply to power plant today is by way of a direct buy from coal mines in Sumatera and Kalimantan island. Such mechanism has some disadvantages, such as the difficulty of power plants to look for coals that meet their requirements in terms of quality and quantity, and distances between coal fired power plants and its coal supplier which could make the total coal procurement cost higher. In addition to direct supply mechanism, there is another alternative option named coal blending mechanism, where coals with various quality from different mines blended in a facility to produce a blended coal with new quality that will meet Coal Fired Power Plant requirements. Coal blending supply mechanism has some advantages, such as Power Plants will be supplied with blended coal that meet their requirements in terms of quality and quantity, and also total coal procurement cost could be minimized by blending coals from nearest mines. Before applying it in power plant coal supply, there are several things to be examined: locations of where Coal Blending Facility (CBF) should be placed, how many facilities should be built, how the coal demand should be allocated, and how many tonnes of coal supplied from each mines to each facility. This research aims to develop a mathematical model to determine the composition of the CBF’s coal supply and determine the optimal CBF location, using the criteria of minimum total coal procurement cost. Problems studied is limited to eight selected new power plants on the northern shore of Java island with total capacity of 10.815 MWs, and also limited for coal suppliers from coal mines in Sumatera and Kalimantan island. The concept of continuous location model (Weber Model) is used during the modeling. There are two models developed, they are Model 01 which is a linear optimization for determination of coal suppliers and nonlinear optimization for determining the location of the CBF, and Model 02 which is a nonlinear optimization for the determination of coal suppliers in parallel of determination of the CBF location. The data processing of both models is done with four coal demand allocation scenarios within two CBFs, Sumatera CBF and Kalimantan CBF. Based on the analysis and discussion done, Model 02 is selected as the basis for problem-solving research and the result is scenario 1 is the scenario with the minimum cost of coal procurement worth $ 1.902.928.872 per year. Coal demand allocation for scenario 1 is 7 steam power plants are served by Sumatera CBF and 1 power plant is supplied by Kalimantan CBF. Location of Sumatera CBF is in Tarahan Coal Terminal and Kalimantan CBF is in South Pulau Laut Coal Terminal.